FRI0422 Estrogen attenuates the disease activity of spondyloarthritis in skg mice. (15th June 2017) - Jeong, H; Bae, E-K; Eun, YH; Kim, IY; Park, E-J; Lee, J; Koh, E-M; Cha, H-S
Abstract : Background: Ankylosing spondylitis is a male-predominant disease, and the male gender is also associated with more severe radiographic damage. Estrogen modulates immune-related processes such as T cell differentiation and cytokine production. Objectives: This study aimed to evaluate the role of estrogen in the disease activity of spondyloarthritis (SpA). The effect of estrogen on the inflammatory cytokines was evaluated. Methods: The effects of estrogen on the development of arthritis were evaluated by performing an ovariectomy and E2 pellet implantation in the zymosan-treated SKG mouse. Clinical arthritis scores were measured and PET-CT was performed to quantify joint inflammation. Total RNA was extracted from the hindpaws and forepaws and the expression of TNFα, IL-6, IFNγ, IL-4, IL-17A, IL-23, Dkk1, and SOST was measured by QuantiGene 2.0 plex assay. Results: Zymosan exposure triggered SpA-like diseases in SKG mice, including peripheral arthritis, spondylitis, dactylitis, enteritis, and psoriatic skin lesions. E2-treated mice showed remarkable suppression of arthritis clinically and little infiltration of inflammatory cells in the Achilles tendon and intervertebral disc. 18 F-FDG uptake was significantly lower in the E2-treated mice. The expression of TNFα, IFNγ, IL-17A, Dkk1, and SOST was significantly reduced in E2-treated mice compared with sham and ovariectomized mice. Conclusions: Estrogen suppressed arthritis development in SpA model of SKG mouse. Results of the study suggest that estrogen may have an anti-inflammatory effect on the disease activity of SpA. Disclosure of Interest: None declared